Isolation and identification of alkaline protease producer halotolerant Bacillus licheniformis strain BA17 - (:unkn) unknown (University of Milan, 2007)
An alkaline protease producer Bacillus licheniformis strain was isolated from Van Lake in Turkey. The strain is Gram positive, aerobic, motile, sporulating rod-shaped bacterium. Spores were ellipsoidal and positioned central in nonswollen sporangium. The cells were able to grow well at a pH range of 5.7-10. The optimal growth temperature was found to be 37 °C. Growth at a wide range of NaCl concentration (from 0 to 20%) showed that BA17 is halotolerant. Main fatty acid composition of BA17 was anteiso-C15:0 and iso-C15:0. The strain was presumptively identified as B. licheniformis according to 16S rDNA gene sequence analysis. The most appropriate medium for the growth and protease production is composed of 0.5% yeast extract, 0.5% NaNO 3, 0.02% MgSO4·7H2O, 0.1% K 2HPO4 and 0.5% maltose. The optimum temperature and pH of the alkaline protease of strain BA17 were found to be 60 °C and pH 11, respectively. The activity was completely lost in the presence of PMSF, suggesting that the preparation contains serine-alkaline protease(s).
Keywords: Alkaline protease; Bacillus licheniformis; Halophiles; Protease production